2011
DOI: 10.1016/j.psychres.2009.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of HIV/AIDS, body mass, and substance abuse on the frontal brain: A P300 study

Abstract: In view of the rising prevalence of an overweight body mass among patients living with HIV/AIDS, clinicians must now be mindful of possible adverse outcomes resulting from the co-occurrence. The present study was designed to examine the additive and interactive effects of HIV/AIDS and an excess body mass, as well as the additional contributions of substance abuse or dependence. The dependent variable was brain function estimated by the measurement of P300 electroencephalographic potentials. P300 potentials wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
0
4
1
Order By: Relevance
“…HIV/AIDS and overweight/obesity were independently associated with increased variability in both readiness potential amplitude and response time accuracy. We did not find evidence of the synergistic interaction previously found in analyses of P300 evoked potentials (Bauer, 2011) and motor function (Bauer et al , 2011). At the risk of accepting the null hypothesis, one could interpret the absence of the interaction as evidence that our time estimation task engages a different neural circuit than selective attention and motor tasks and this circuit is differently challenged by these two factors.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…HIV/AIDS and overweight/obesity were independently associated with increased variability in both readiness potential amplitude and response time accuracy. We did not find evidence of the synergistic interaction previously found in analyses of P300 evoked potentials (Bauer, 2011) and motor function (Bauer et al , 2011). At the risk of accepting the null hypothesis, one could interpret the absence of the interaction as evidence that our time estimation task engages a different neural circuit than selective attention and motor tasks and this circuit is differently challenged by these two factors.…”
Section: Discussioncontrasting
confidence: 92%
“…One example of amplification was reported by our group (Bauer, 2011) from a study that examined P300 electroencephalographic potentials during a simple selective attention task. The results revealed a statistically significant delay in P300 latency over the frontal brain among HIV-1 seropositive versus seronegative participants.…”
Section: Introductionmentioning
confidence: 80%
“…Contrary to the initial hypothesis, the current study found no evidence of an interaction between HIV and history of CD on neurocognitive performance, nor evidence of interactive changes in measures of brain integrity in participants with HIV and history of CD. Although previous functional neuroimaging studies have revealed synergistic CD+/HIV+ alterations in executive control-related brain circuitry (Bauer, 2011; Bell et al, 2020; Meade et al, 2016; Meade et al, 2017; Wakim et al, 2021), only three studies to date have employed structural MRI to examine the possible interactive effects of HIV and substance dependence on brain-based measures using structural neuroimaging. Jernigan and colleagues used structural MRI to examine the interaction between a history of methamphetamine (meth) dependence and HIV in meth-abstinent participants, finding largely independent effects of each factor on cerebral brain volume estimates (Jernigan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Two primary findings were consistent across all reviewed studies: First, a significant reduction in EEG alpha power was observed for HIV groups recorded during resting state under both eyes open and eyes closed condition ( Babiloni et al, 2014 , 2015 , 2016a , 2016b ), and during auditory oddball task ( Polich et al 2000 ). Second, HIV groups exhibited decreased amplitude and increased latency of the P300 and the Late Positive Potential (LPP) components ( Polich et al, 2000 ; Polich and Basho, 2002 ; Chao et al, 2004 ; Bauer, 2011 ; Olichney et al, 2011 ; Papaliagkas et al, 2011 ). Additionally, decreased amplitude and increased latency were also reported for the P100, N100, P200, N200 and N400 components ( Fernández-Cruz and Fellows 2017 ), but these results were reported less frequently.…”
Section: Introductionmentioning
confidence: 99%